Stability Analysis of a Stochastic Model for Prey-Predator System with Disease in the Prey - Mukherjee, D. (Nonlinear Analysis: Modelling and Control, 2003)
In this paper we consider a prey-predator system where the prey population is infected by a microparasite. Local as well as global stability properties of the interior equilibrium point are discussed. The stochastic stability properties of the model are investigated, suggesting that the deterministic model is robust with respect to stochastic perturbations.